1997
DOI: 10.1016/s0020-7292(97)00113-6
|View full text |Cite
|
Sign up to set email alerts
|

Routine colposcopic evaluation of patients with persistent inflammatory cellular changes on Pap smear

Abstract: Colposcopically-directed biopsies of the cervix are indicated even when inflammatory cellular changes without atypia persist despite therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 1 publication
1
18
0
2
Order By: Relevance
“…Similar results were reported by Secken et al [4] The incidence is lower than that reported by Sandmire (35.1%) [11] and Reiter (25.3%). [12] Again this could be explained by the predominance of healthy cervix among the women included in the study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar results were reported by Secken et al [4] The incidence is lower than that reported by Sandmire (35.1%) [11] and Reiter (25.3%). [12] Again this could be explained by the predominance of healthy cervix among the women included in the study.…”
Section: Discussionsupporting
confidence: 91%
“…However, due to the low sensitivity and high false negative rate of Pap smear there is a possibility that an inflammatory Pap smear may miss cervical premalignant changes. Since the incidence of inflammation on Pap smear is very high (14%-19%) [4][5][6][7] it may not be possible to subject all patients with inflammation to colposcopy or HPV DNA testing. This study was designed to evaluate whether persistent inflammatory changes on Pap smear could be the first indication of premalignant changes in the cervix and whether further evaluation by colposcopy would help to triage these women.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of premalignant lesions of cervix in various studies range from 8.15% to 35.2%. 12,13,25,27,29,30 The main goal of cervical screening is to identify women with premalignant lesions of cervix which are precursors of invasive cancer and require treatment, thus ultimately decreasing morbidity and mortality due …”
mentioning
confidence: 99%
“…Varios estudios indican que la citología infl amatoria puede estar asociada a procesos inespecífi cos del cérvix, o secundarios a infecciones del tracto genital inferior, por C. trachomatis, Candida Albicans, Tricomonas vaginalis, vaginosis bacteriana, virus Herpes simplex o a la presencia del dispositivo intrauterino (31)(32)(33)(34). La citología infl amatoria también puede estar relacionada a la presencia del VPH, donde la respuesta inmune en el huésped promueve el reclutamiento de células infl amatorias (35,36). Se ha descrito que la infección por VPH puede afectar cerca del 10 % de las mujeres sin alteraciones en la citología (37).…”
Section: Discussionunclassified
“…Se ha descrito que la infección por VPH puede afectar cerca del 10 % de las mujeres sin alteraciones en la citología (37). Sin embargo, la utilidad de la citología infl amatoria como predictor de lesión premaligna para CCU, ha sido rechazada por algunos autores (38,39), otros consideran que la citología infl amatoria persistente debe ir acompañada de colposcopia, debido a que se encuentran anormalidades en la biopsia desde un 20 % hasta un 70 % (35,40,41).…”
Section: Discussionunclassified